UPAYA ORANGTUA MENGENDALIKAN EMOSI NEGATIF PADAANAK USIA DINI - Astri, Widya - (Bimbingan dan Konseling, 2014)
This research was motivated by the lack of the ability of parentsto control the negative emotions in early childhood. This study aimed to look at the efforts of parents to control the negative emotions in early childhood at Koto Kaciak Kelurahan Mata Air Kecamatan Padang Selatan, with a focus on research that parental efforts to control the emotion of fear and emotional upset early childhood. This research was conducted with a qualitative descriptive approach that describes the symptoms, facts andreality in the field which was about the efforts of parents to control the negative emotions of early childhood. As for there search informants are: Parents who have children and grumpy nervy 4-6 years old, as well as uncle/aunt of early childhood. Instruments that researchers use in this study were interview sand documentation. Data analyz with phaseis a data reduction, data presentation and conclusion. Results ofthe study revealed that parents are lessable to deal with children who are scared and angry. Motheras a parent that is closest to the child often feels upset in her face to feel the emotions of excessive fear and anger. Resent ment is like a mother, threatens the child, giving a negative callon the child, and cold the child. In addition, some times the mother also choose to give in and follow their children so that their children can be quiet and not whining anymore.